Sinergi Manajemen Konflik dan Motivasi dalam Meningkatkan Kinerja SDM Pendidikan Islam - Ulfi Maula Saniya; Syifa Fauzia; Ahmad Fatah Yasin; Indah Aminatuz Zuhriyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic educational institutions face various challenges in human resource management, such as internal conflicts, low work motivation, and suboptimal performance of educators. These issues impact the effectiveness of institutions in achieving educational goals. This article aims to analyze how the synergy between conflict management and work motivation can improve human resource performance in Islamic educational institutions based on Islamic values. The issues examined include how conflict management and motivation contribute to performance improvement, as well as how Islamic values can be used as a basis for their management. The method used is a literature study by reviewing various relevant literature from journals, books, and previous research results. The results of the study show that conflicts that are managed constructively and motivation that is built on the basis of Islamic spiritual values can create a productive and sustainable work culture. The synergistic integration of the two can encourage an improvement in work ethic, teamwork, and the quality of educational services. This article provides a theoretical contribution to the development of HR management strategies in Islamic educational institutions based on Sharia values.